2014
DOI: 10.1136/bcr-2014-204409
|View full text |Cite
|
Sign up to set email alerts
|

Fatal cardiac involvement complicating antisynthetase syndrome

Abstract: A 35-year-old Afro-Caribbean woman presented with dyspnoea, urticarial rash and myalgia 1 month after treatment for a community-acquired respiratory tract infection. Investigations revealed raised antisynthetase antibodies, lung fibrosis and an inflammatory myopathy. The patient was diagnosed with antisynthetase syndrome (ASS) and started on immunosuppressive medication. Despite treatment she died 4 weeks after presentation from a fulminant cardiomyopathy. ASS is a rare condition and is not typically associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…A registry of 352 ASS cases found 12 patients with ASS-associated myocarditis, of whom 75% had full recovery following appropriate therapy. Another case published in 2014 described fatal cardiac involvement 7. Myocarditis in ASS is rare and may be the first presenting feature of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A registry of 352 ASS cases found 12 patients with ASS-associated myocarditis, of whom 75% had full recovery following appropriate therapy. Another case published in 2014 described fatal cardiac involvement 7. Myocarditis in ASS is rare and may be the first presenting feature of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed a prevalence of myocarditis in aSS of 3.4%. However, the limitation of this study is inherent to its retrospective design, and these data could have been either underestimated due to severe undiagnosed cases 7 or overestimated due to recruitment bias (all centers being tertiary care centers). There have been no reports to date in the literature providing this specific figure for aSS, but it is comparable to what has been reported for other inflammatory myopathies.…”
Section: Discussionmentioning
confidence: 99%
“…This latter manifestation seems to be particularly rare in aSS, with only a few case reports published to date. 7 , 8 Although potentially severe, this condition could be underestimated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-synthetase antibodies have also been detected in a case of cryptogenic organizing pneumonia (93) and in association with uncommon clinical manifestations such as aphthous-like ulcerations and xerostomia (94). As for their prognostic significance, anti-PL-12 and PL-7 antibodies are related to lower survival rates (81,82), and anti-EJ antibodies have been reported in a case of fatal myocarditis in anti-synthetase syndrome (95).…”
Section: Autoabs In Polymyositis/dermatomyositis (Pm/dm) and In The Amentioning
confidence: 99%